PENGGUNAAN PERANGKAP UNTUK PENGENDALIAN HAMA TIKUS SAWAH (RATTUS RATTUS ARGENTIVENTER) - Lestari Wibowo, I Gede Swibawa, dan Tejo Muryanto . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2003)
The use of traps to control lowland rats. The lowland rat (Rattus rattus argentiventer ) is one of the importance pests of rice in Indonesia. The rat may cause serious damage on rice and other crops. This study was aimed to determine the affectivity of rat trappings. Traps were set in Pekalongan Central Lampung, from October to December 2002. The treatments were arranged in a factorial experiment in randomized complete block design. The first factor was the type of traps (bamboo trap and wired “bubu” trap) while the second factor was the location of traps (rice field, swamp, tertiary irrigation canal, and rice plot borders). The catches show that there were no interaction between the trap type and trap location. In addition, more rats were caught in bamboo than those in wired “bubu” trap. The highest number of rat catches was from the swamp area.